Respuesta :

logo88
s= -3 and 0 
6s²+18=0
6s(s+3)=0 
6s=0 s+3=0
s=0 and s= -3

The factors of the quadratic equation are s = 0, and s = -3.

Given that,

  • The quadratic equation is [tex]6s^2 + 18s = 0[/tex]

We need to find the factors of the above equation.

So,

[tex]6s^2 + 18s = 0\\\\6s(s + 3) = 0\\[/tex]

So,

6s = 0, and s + 3 = 0

s = 0, and s = -3

Therefore we can conclude that the factors of the quadratic equation are s = 0, and s = -3.

Learn more about the quadratic equation here: brainly.com/question/17718371

ACCESS MORE